The Book of Jeremiah : composition, reception, and interpretation - Lundbom, Jack R. (Vetus Testamentum, Supplements, 2018)
Written by leading experts in the field, The Book of Jeremiah: Composition, Reception, and Interpretation offers a wide-ranging treatment of the main aspects of Jeremiah. Its twenty-four essays fall under four main sections. The first section contains studies of a more general nature, and helps situate Jeremiah in the scribal culture of the ancient world, as well as in relation to the Torah and the Hebrew Prophets. The second section contains commentary on and interpretation of specific passages (or sections) of Jeremiah, as well as essays on its genres and themes. The third section contains essays on the textual history and reception of Jeremiah in Judaism and Christianity. The final section explores various theological aspects of the book of Jeremiah.